2019
DOI: 10.1111/1365-2664.13447
|View full text |Cite
|
Sign up to set email alerts
|

Organic farming positively affects honeybee colonies in a flower‐poor period in agricultural landscapes

Abstract: 1. Conventional farming has been implicated in global biodiversity and pollinator declines and organic farming is often regarded as a more ecological alternative.However, the effects of organic farming on honeybees remain elusive, despite honeybees' importance as pollinators of crops and wild plants.2. Using 6 years of data from a large-scale study with fortnightly measurements of honeybee colony performance traits (10 apiaries per year distributed across a 435 km 2 -large research site in France), we related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Organic agriculture has the potential to mitigate adverse effects of intensive farming. Species richness, functional diversity and abundance of a wide-range of taxa are often higher on organic than conventional farms ( but see Brittain et al, 2010;Gallé et al, 2019;Gomiero et al, 2011;Hole et al, 2005;Holzschuh et al, 2008;Katayama et al, 2019;Krauss et al, 2011;Schneider et al, 2014;Wintermantel et al, 2019). Positive effects of organic agriculture on biodiversity vary among landscape and crop types, levels of crop diversification.…”
Section: Organic Agriculturementioning
confidence: 99%
“…Organic agriculture has the potential to mitigate adverse effects of intensive farming. Species richness, functional diversity and abundance of a wide-range of taxa are often higher on organic than conventional farms ( but see Brittain et al, 2010;Gallé et al, 2019;Gomiero et al, 2011;Hole et al, 2005;Holzschuh et al, 2008;Katayama et al, 2019;Krauss et al, 2011;Schneider et al, 2014;Wintermantel et al, 2019). Positive effects of organic agriculture on biodiversity vary among landscape and crop types, levels of crop diversification.…”
Section: Organic Agriculturementioning
confidence: 99%
“…Observed trends in wild pollinators have been mostly linked with changes in land management 12 , climate change 13 , and agrochemical use 14 , although these analyses are largely restricted to Europe and North America. Restoring or diversifying habitats and reducing management pressures such as pesticides and grazing have been shown to positively affect wild pollinator populations and managed honeybee health [15][16][17] .…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have evaluated how colony growth, honey production and survival correlates with particular land use practices, such as the percentage of agricultural land or the percentage of certain crops in the area surrounding the hive 16 19 . However, while several studies have indicated that honey bees show reduced growth or higher mortality with increasing urban or agricultural land use 16 , 17 , 20 , others have found that agricultural land use is positively correlated with colony survival 18 .…”
Section: Introductionmentioning
confidence: 99%